Diagnosis of Cephalopelvic Disproportion or Failure to Progress of Labor in Rajavithi Hospital Compare with The Criteria of Royal Thai College of Obstetricians and Gynaecologists - Ekachai Kovavisarach; Paweena Buddeewong (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective:To evaluate the correlation of the clinical criteria for cephalapelvic disproportion (CPD) or failure to progress of labor (FPL) in women underwent cesarean delivery with the criteria endorsed by the Royal Thai College of Obstetricians and Gynaecologists. (RTCOG)Material and Method: Two hundred and sixty one women underwent cesarean section due to CPD or FPL in Rajavithi Hospital from June 1st 2008 to May 31st, 2009 were retrospectively enrolled. The correlation between both criteria were analyzed using the criteria endorsed by RTCOG.Results:The correlation rate of the clinical criteria for diagnosis of CPD or FPL in women underwent cesarean section due to CPD or FPL with the criteria endorsed by the RTCOG was 82.00%. The correlation in private cases was significantly lower than those in ward cases. (53.2% vs 85.5%, p < 0.01). Maternal age, Bishop score, cervical dilatation when diagnosis of CPD or FPL by clinical or RTCOG criteria were statistic significant difference between groups.Conclusion:The correlation of clinical criteria and RTCOG criteria for diagnosis of CPD or FPL was higher (82.00%)The correlation rate in private cases was lower than those in ward cases. (53.2 % vs 85.5%, p < 0.01)